Full-Scale Structural and Nonstructural Building System Performance during Earthquakes: Part II – NCS Damage States. Issue 2 (May 2016) - Pantoli, Elide; Chen, Michelle C.; Wang, Xiang; Astroza, Rodrigo; Ebrahimian, Hamed; Hutchinson, Tara C.; Conte, Joel P.; Restrepo, José I.; Marin, Claudia; Walsh, Kenneth D.; Bachman, Robert E.; Hoehler, Matthew S.; et al.
Nonstructural components and systems (NCSs) provide little to no load bearing capacity to a building; however, they are essential to support its operability. As a result, 75–85% of the initial building financial investment is associated with these elements. The vulnerability of NCSs even during low intensity earthquakes is repeatedly exposed, resulting in large economic losses, disruption of building functionality, and concerns for life safety. This paper describes and classifies damage to NCSs observed during landmark shake table tests of a full-scale five-story reinforced concrete building furnished with a broad variety of NCSs. This system-level test program provides a unique dataset due to the completeness and complexity of the investigated NCSs. Results highlight that the interactions between disparate nonstructural systems, in particular displacement compatibility, as well as the interactions between the NCSs and the building structure often govern their seismic performance.